Pengaruh Kompensasi, Disiplin Kerja, Dan Kepuasan Kerja Terhadap Kinerja Karyawan BUMN Pada PT Pos Indonesia (Persero) Di Kota Ambon - Nila Wati; Ferdy Leuhery (Soso-Q : Jurnal Manajemen, 2021)
ABSTRACT This study aims to determine the extent of the influence of compensation, work discipline and job satisfaction on the performance of BUMN employees at PT. Pos Indonesia in Ambon City. The study was conducted on employees at PT Pos Indonesia with the population in this study were all employees of BUMN PT. Pos Indonesia totaling 30 people and using saturated samples were all used as samples in this study, the data collection techniques used were questionnaires and interviews. The data analysis method used is multiple linear regression analysis using SPSS for windows version 23. The hypothesis was tested using the F test and t test, the results showed that (1) Compensation had a significant or significant effect on the performance of BUMN PT. Pos Indonesia (2) Work discipline has a significant or significant effect on performance (3) Job Satisfaction has a significant effect on performance (4) Compensation, work discipline and job satisfaction simultaneously affect the performance of employees of BUMN PT Pos IndonesiaKeywords: Compensation, Work Discipline and Job Satisfaction on Employee Performance.